THE EUPHROSYNE FAMILY'S CONTRIBUTION TO THE LOW ALBEDO NEAR-EARTH ASTEROIDS - Masiero, Joseph R.; Carruba, V. [UNESP]; Mainzer, A.; Bauer, J. M.; Nugent, C. (Iop Publishing Ltd, 2015)
The Euphrosyne asteroid family is uniquely situated at high inclination in the outer Main Belt, bisected by the n6 secular resonance. This large, low albedo family may thus be an important contributor to specific subpopulations of the near-Earth objects. We present simulations of the orbital evolution of Euphrosyne family members from the time of breakup to the present day, focusing on those members that move into near-Earth orbits. We find that family members typically evolve into a specific region of orbital element-space, with semimajor axes near similar to 3 AU, high inclinations, very large eccentricities, and Tisserand parameters similar to Jupiter family comets. Filtering all known Near-Earth objects (NEOs) with our derived orbital element limits, we find that the population of candidate objects is significantly lower in albedo than the overall NEO population, although many of our candidates are also darker than the Euphrosyne family, and may have properties more similar to comet nuclei. Followup characterization of these candidates will enable us to compare them to known family properties, and confirm which ones originated with the breakup of (31) Euphrosyne.
Keywords: minor planets; asteroids: general